ENT 530 Social Media Portfolio / Anis Najiha S.Ramli - S.Ramli, Anis Najiha (2019)
Beauty With Miss A (BWMA) is an online business that focuses on selling a cosmetic product. My business have been registered in Companies Commission of Malaysia (SSM). The product name is Mary Kay. The specialty of Mary Kay Brand is I am focusing and suggesting a good products as an agent that can be used by all people especially woman out there. Basically, Mary Kay have so many kind of skincare that suitable in certain age and makeup set.